Lifestyle-Related Diseases of the Digestive System: A New In Vitro Model of Hepatitis C Virion Production: Application of Basic Research on Hepatitis C Virus to Clinical Medicine - Satoru Saito; Theo Heller; Masato Yoneda; Hirokazu Takahashi; Atsushi Nakajima; Jake T. Liang (Elsevier, 2007)
The hepatitis C virus (HCV) is an enveloped virus with a single positive-strand RNA genome of about 9.6 kb. It is a major cause of liver disease worldwide. Clear understanding of the viral life cycle has been hampered by the lack of a robust cell culture system. While the development of the HCV replicon system was a major breakthrough, infectious virions could not be produced with the replicon system. Recently, several groups have reported producing HCV virions using in vitro systems. One of these is a replicon system, but with the special genotype 2a strain JFH-1. Another is a DNA transfection system, with the construct containing the cDNA of the known infectious HCV genotype 1b flanked by two ribozymes. The development of these models further extends the repertoire of tools available for the study of HCV biology, and in particular, they may help to elucidate the molecular details of hepatitis C viral assembly and release. This review discusses the progression of experimental strategies related to HCV and how these strategies may be applied to clinical medicine. Keywords:: life style-related disease, hepatitis C virus (HCV), replication, in vitro system, HCV-like particle, particle